THE IMPACT OF INDIA’S ECONOMY ON THE DEVELOPMENT OF SEAPORTS - Leszek MINDUR (Scientific Journal of Silesian University of Technology. Series Transport)
India’s diversified economy includes traditional and modern agriculture, crafts, modern industries and a variety of services. In 2017, almost half (48.93%) of India’s GDP was generated by the service sector, whereas the industrial sector accounted for 26.16% and agriculture 15.45%. Despite a shortterm economic downturn caused by a demonetisation and implementation of compulsory tax on goods and services, the continued favourable economic growth, including sustainable growth of the gross domestic product, revenue per capita, private consumption and public investment, as well as the improvement of other economic indicators, for example, car sales indicate that India’s macroeconomic conditions are generally stable. Structural reforms introduced by the government contribute to enhanced productivity among domestic businesses and attract more foreign direct investment. Due to its geographical location, India has been using sea transport to promote its international trade. However, with too few deep-sea ports and limited cargo handling capacity, its seaports can handle only some of the largest intercontinental ships. This article discusses India’s economic situation, with particular regard to the GDP growth in 2000-2017 and foreign trade. The analysis covers growth in cargo handling in main ports in India in 2000-2018. It discusses the port development project of Sagarmala introduced by the Government of India in 2015. The project is expected to solve problems associated with the performance of Indian ports and strengthen the Indian maritime sector to meet the ever-growing demand for goods transported by sea.